Дослідження впливу складу елегазу на струм тестового сигналу пристрою контролю швидкісних характеристик високовольтних вимикачів - Кутін, В.М.; Рубаненко, О.Є.; Мисенко, С.В. (Технічна електродинаміка, 2012)
The necessity of improving diagnostic methods and means of high-voltage circuitteley to determine the velocity and acceleration of the moving contacts of the switch at work. The analysis of the influence of the technical condition of sulfur hexafluoride in determining the speed characteristics of the circuit breaker and the distance between the moving and non-movable contacts. The dependence of the dielectric constant of the gas mixture of nitrogen and sulfur hexafluoride, depending on their ratio.